2015
DOI: 10.1186/s12886-015-0166-0
|View full text |Cite
|
Sign up to set email alerts
|

Rates of glaucomatous visual field change before and after transscleral cyclophotocoagulation: a retrospective case series

Abstract: BackgroundThe primary goal of glaucoma treatment is to lower and control intraocular pressure (IOP) and thereby prevent functional deterioration. For glaucomas that are refractory to medical and incisional surgical therapies, transscleral diode cyclophotocoagulation (TCP) is a well-established procedure to effectively decrease IOP. This study investigated rates of visual field (VF) change in patients with glaucoma before and after TCP.MethodsThis retrospective case series investigated rates of VF changes in gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Eyes not experiencing an IOP spike during the first 3 hr postsurgery show a greater IOP lowering at 3 months (Uppal et al 2015). Despite these potential IOP spikes, the rates of glaucomatous visual field loss do not significantly change after CW‐TSCPC, even in case of severe end‐stage glaucoma (Bleisch et al 2015). A possible bias could be that the central corneal thickness (CCT) measured with the Orbscan increases during the 10 days after CW‐TSCPC and returns to its prelaser level at 1 month, which could be due to inflammation and transient endothelial dysfunction induced by cyclophotocoagulation (Arikan et al 2008).…”
Section: Cw‐tscpc and Ecpmentioning
confidence: 99%
“…Eyes not experiencing an IOP spike during the first 3 hr postsurgery show a greater IOP lowering at 3 months (Uppal et al 2015). Despite these potential IOP spikes, the rates of glaucomatous visual field loss do not significantly change after CW‐TSCPC, even in case of severe end‐stage glaucoma (Bleisch et al 2015). A possible bias could be that the central corneal thickness (CCT) measured with the Orbscan increases during the 10 days after CW‐TSCPC and returns to its prelaser level at 1 month, which could be due to inflammation and transient endothelial dysfunction induced by cyclophotocoagulation (Arikan et al 2008).…”
Section: Cw‐tscpc and Ecpmentioning
confidence: 99%
“…[10] Contrary to this, Bleisch found that the visual fields continued to worsen after cyclophotocoagulation and Hasan reported cyclophotocoagulation is less effective that trabeculectomy in POAG. [ 21,22] Abdull found TSCPC to be safe and effective in cases of primary glaucoma where regular follow-up is not critical. [12] Stanca described a 'slow-burn' technique which can be used in eyes with better vision.…”
Section: Discussionmentioning
confidence: 99%
“…TSCPC has proved to be a successful surgical method to lower IOP [ 3 5 ] while not increasing visual field loss. [ 6 ] However, many ophthalmologists hesitate to perform this procedure due to its painful nature and high risk of complications such as hypotony and phthisis bulbi. [ 7 , 8 ] Trabeculectomy has often been considered the most effective method in controlling glaucoma, but the number of trabeculectomies performed worldwide is steadily decreasing.…”
Section: Introductionmentioning
confidence: 99%